2023
DOI: 10.1186/s12893-023-02026-2
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of risk factors for non-superficial surgical site infection following spinal surgery

Abstract: Background Surgical site infection (SSI) is the most common complications in spinal surgery. In SSI, non-superficial surgical site infections are more likely to result in poor clinical outcomes. It has been reported that there are multiple factors contributing to postoperative non-superficial SSI, but still remains controversial. Therefore, the aim of this meta-analysis is to investigate the potential risk factors for non-superficial SSI following spinal surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Obesity as a risk factor for SSI has been extensively studied in the adult population. Several meta-analyses have been conducted, such as the one by Liu et al, which found that obesity increased the risk of non-superficial SSI after spinal surgery [ 10 ]. Similarly, Liu et al reported that BMI ≥30 kg/m 2 resulted in significantly higher SSI after colorectal surgery [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity as a risk factor for SSI has been extensively studied in the adult population. Several meta-analyses have been conducted, such as the one by Liu et al, which found that obesity increased the risk of non-superficial SSI after spinal surgery [ 10 ]. Similarly, Liu et al reported that BMI ≥30 kg/m 2 resulted in significantly higher SSI after colorectal surgery [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…Still, they evaluated the impact of obesity in a specific type of surgery. Some meta-analyses have gathered data but remain focused on certain complications for a specific surgical procedure [ 10 ].…”
Section: Introductionmentioning
confidence: 99%